Selective absorption enhancement in organic solar cells using light incoupling layers - Meiss, J; Furno, M; Pfuetzner, S; Leo, K; Riede, M (American Institute of Physics, 2010)
We show that capping layers of tris-(8-hydroxy-quinolinato)-aluminum Alq enable increased absorption and photocurrent in organic solar cells (OSCs) when using transparent metal films as top electrodes. Furthermore, by varying the capping layer thickness, the optical field in the OSC is tuned for selective wavelengths, opening a possibility of influencing the external quantum efficiency for specific absorber materials. It is described how a second maximum of the optical field intensity can be utilized, which is a concept significant for tandem solar cells. Indium tin oxide (ITO)-free OSCs are presented which show the influence of capping layer on efficiency, saturation, fill factor, and open-circuit voltage, with numerical calculations supporting the experimental evidence of layer-selective enhancement. Copyright 2010 American Institute of Physics.